The Influence of Peppermint Aromatherapy on Reducing Uremic Pruritus in Patients with Chronic Kidney Disease Undergoing Hemodialysis - Sembiring, Friska; Nasution, Siti Saidah; Ariani, Yesi (Jurusan Keperawatan FIKES UNSOED, 2021)
Uremic pruritus is one of the chronic renal failure patients’ complaints, which is an uncomfortable and itchy sensation with multifactorial causes. Peppermint complementary therapy is an essential oil with the main component of menthol (50-60%), which provides a cold sensation to the skin. The instrument used in this quasi-experimental study was demographic data and the 5-D itch scale questionnaire. The total sample was 98 participants. The intervention was carried out by administering topical peppermint essential oil. The results showed that the uremic pruritus scale decreased to a mild degree of 51.0%. After being tested by Wilcoxon and Mann-Whitney statistical tests, the intervention group had a p-value of 0.000 <p = 0.05 and in the control group there was a p-value of 0.102 so there was an effect of giving peppermint aromatherapy in reducing uremic pruritus. Peppermint aromatherapy is safe to use and is easy to obtain so, therefore, it can be applied topically to improve coping strategies for patients who experience uremic pruritus.